Standardising assessment instruments and care planning in Ireland. (4th March 2014) - Van Lente, Eric; Power, Martin
Abstract : Purpose: – Scoping of instruments in use for assessment of needs and the practices that surround care planning in residential care for older people in Ireland, in the wake of the introduction of national standards. The paper discusses these issues. Design/methodology/approach: – Survey of care providers using an online/postal questionnaire, developed from the domains of need outlined in the standards. Findings: – There is wide variation in the use of standardised instruments for assessment. Within some domains, standardised instruments enjoy near universal usage. However, within other domains, standardised instruments are often absent, external professional input and/or guidelines dominate and/or instruments have been adapted in-house. Practices surrounding care planning are largely homogeneous and the preserve of medical professionals. Research limitations/implications: – This research was confined to the Republic of Ireland, limiting generalisation. The self-selecting nature of participants must also be considered. Further research could include, examining how, over time, the standards are shaping care practice, particularly in relation to interdisciplinary working and person-centred care. Practical implications: – The non-prescriptive nature of the standards presents a challenge to care providers in selecting appropriate standardised instruments for assessment. In addition, medical dominance of care planning limits the extent to which care plans can enhance the provision of interdisciplinary and person-centred care. Originality/value: – This paper contributes to a growing literature on standardisation of assessment and care planning, provides a reference point for comparison with other nations and, in an Irish context, addresses an area that has received little attention to-date. As such, it is of interest to practitioners, care providers and regulators.